THE STRUGGLE FOR LIFE OF RAY FERRIER IN WAR OF THE WORLDS: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - DEWI, PURNAMA SARI (2006)
The problem statement of this study is how Ray Ferrier struggles to save his children in War of the Worlds. There are two objectives of the study. The first, the writer tries to analyze the structural elements of the film. The second objective is to analyze the major character of the film based the individual psychological approach. The object of research paper is the film entitled War of the Worlds. This study belongs to qualitative study. In this method, the writer uses two data sources: primary data and secondary data. The primary data and the object of the study is the major character, Ray Ferrier in War of the Worlds. The secondary data are from internet data, etc that are related to this study. The technique of data analysis in this study is descriptive technique. The result of the study shows that some aspects of Individual Psychology influence Ray Ferrier's struggle to save his children in War of the worlds and the theme of this film is the struggle for life in war of tripods which representative by one of American family, Ray Ferrier's family. The struggle for life, especially to save his children and generally to save the civilians.